Criteria for acetylcysteine treatment and clinical outcomes after paracetamol poisoning. Issue 3 (May 2012) - Waring, W Stephen
Acetylcysteine is an effective antidote for paracetamol (acetaminophen) poisoning, but different treatment criteria exist internationally. In the UK, acetylcysteine is indicated by paracetamol concentrations higher than the Prescott nomogram or higher than 50% of the nomogram in patients with increased susceptibility to liver toxicity. In the USA, a single '150-line' nomogram has been used that removes the need for additional clinical risk assessment. The latter approach has recently been adopted in Australia, New Zealand and elsewhere. Few data exist to allow direct comparison of these different international approaches. An existing database of 1191 patients admitted to hospital after paracetamol overdose identified that the 4-h equivalent paracetamol concentration was: ≥200 mg/l in 163 patients (15.6%; 95% CI: 13.3–18.2%), ≥150 mg/l in 264 (24.3%; 95% CI: 21.5–27.5%) and ≥100 mg/l in 426 patients (39.3%; 95% CI: 35.6–43.2%), and acute liver injury occurred in 3.7% (95% CI: 1.4–8.0%), 2.3% (95% CI: 0.8–5.0%) and 1.9% (95% CI: 0.8–3.7%), respectively. The different indications for acetylcysteine used by the UK and USA would result in similar numbers of patients treated, although the criteria would define patients with different characteristics and patterns of overdose. The relative merit of these different international approaches to acetylcysteine administration is considered in this article.